The Effect Of Project Based Learning On Creative Thinking Skills For Teachers - Anisa'ul Indah Mutiasari; Mustaji Mustaji; Lamijan Hadi Susarno (UNDIKMA, 2023)
The success of a program is closely related to the quality of the plans made. The inability of someone to plan a program will undoubtedly tend to fail. Likewise, educational success is closely associated with quality learning processes. This research is a case study analysis that explores a system that is bound or a case (or it could be several cases) that occurred over a certain period through in-depth and detailed data collection from various sources of information that can be trusted for the truth of the testimony. This research aims to determine the effect of project-based learning on students' creativity in preparing learning designs. This study used an experimental type using a one-group pretest-posttest technique. The research was conducted at Ketintang Vocational High School Surabaya, involving ten multimedia teachers and collecting data using practice tests. The results and analysis of the data obtained in the independent sample t-test get t count > t table. If so, project-based learning affects teacher creativity.